VD_FINDINFO Décision / 2014 / 946 vom 22. Mai 2014 - VD Tribunal cantonal (2014)
RETRAITVOIE DE DROIT, INDEMNITÉEN GÉNÉRAL, DÉFENSE D'OFFICE, DÉCISION SUR FRAIS | 135 CPP (CH), 386 al. 2 let. a CPP (CH), 44 PPMin